Steering E-Government Projects from Failure to Success: Using Design-Reality Gap Analysis as a Mid-Implementation Assessment Tool - and Lessa, Lemma; Negash, Solomon; Belachew, Mesfin (Emerging Issues and Prospects in African E-Government:, 2014)
There are many e-government failures in developing countries. Most studies look at these after the event (post hoc), but this chapter takes an original approach to look mid-implementation (durante hoc) in order to provide recommendations for improvement. The authors chose a partial failure/partial success land management information system being implemented in one Ethiopian city. The project has made retrieval of land information quicker and simpler but is only partly implemented, and is still—on occasion—circumvented by public servants for personal gain. They used design-reality gap framework to understand why the project had partly failed. The authors used the design-reality gap analysis to propose an action plan that would help institutionalise the system, steering it from partial failure to success. They demonstrate the value of this framework as a tool for mid-implementation analysis of e-government projects. The authors recommend its usage on other ongoing e-government projects in developing countries.